Pengembangan E-learning Berbasis Moodle pada Pembelajaran Tematik Bagi Siswa Kelas IV MI Mangunsari Salatiga - Hidayati, Sri Utami; Maslikhah, Maslikhah (QUALITY, 2022)
Development of Moodle-Based E-learning in Thematic Learning for Fifth Grade Students of Elementary School of Mangunsari Salatiga. This study aims to develop Moodle-based E-learning in thematic learning to improve fourth-grade student learning outcomes at MI Mangunsari Salatiga City. This research is a type of research and development (R & D) which refers to the concept of thinking of Borg and Gall, which Sugiyono has adapted. The subjects involved in this study were teachers and fourth-grade students at MI Mangunsari Salatiga. Data collection was done through interviews. The object of this research is Moodle on the thematic learning of the theme of my ideals at MI Mangunsari, Salatiga City. Technical analysis of data using a quantitative descriptive approach with data collection using interviews, questionnaires and learning outcomes tests. The product form in this study is Moodle hilemoclassroom as a program with validation test results using a t-test with an average score of 60.84 at the pretest time and increasing to an average of 73.80 after the posttest. The design validation test by IT and material experts obtained a score of 45 with a percentage of 90%, a very feasible category. In contrast, the results of material validation obtained a score of 90 with a percentage of 94%, a very decent percentage. While the results of the paired samples test t-test, data obtained that = 0.05 is greater than the value of Sig. (2-tailed) which is 0.000, then Ho is rejected, and Ha is accepted. Based on the research results, Moodle-based E-learning in thematic learning can improve the learning outcomes of fourth-grade students at MI Mangunsari, Salatiga City. Penelitian ini bertujuan untuk mengembangkan pembelajaran E- learning berbasis Moodle pada pembelajaran tematik untuk meningkatkan hasil belajar siswa kelas IV di MI Mangunsari Kota Salatiga. Penelitian ini merupakan jenis penelitian dan pengembangan (R & D) yang mengacu pada konsep pemikiran Borg dan Gall yang sudah disesuaikan oleh Sugiyono. Subjek yang terlibat dalam penelitian ini adalah guru dan siswa kelas IV di MI Mangunsari Salatiga. Pengumpulan data dilakukan melalui wawancara. Obyek penelitian ini Moodle pada pembelajaran tematik tema cita citaku di MI Mangunsari Kota Salatiga. Teknis analisa data menggunakan pendekatan deskriptif kuantitatif dengan pengumpulan data menggunakan wawancara, kuosioner dan tes hasil belajar. Bentuk produk pada penelitian ini adalah Moodle hilemoclassroom sebagai program dengan hasil uji validasi menggunakan t test dengan capaian skor rata-rata 60,84 pada saat pretest dan meningkat menjadi rata-rata 73,80 setelah dilaksanakan posttest. Uji Validasi desain oleh ahli IT dan ahli materi diperoleh skor sebesar 45 dengan presentase 90 persen dengan kategori sangat layak, sedangkan hasil validasi materi diperoleh skor 90 dengan presentase 94 % dengan presentase sangat layak. Sedangkan hasil uji t-test uji paired samples test diperoleh data bahwa α = 0,05 lebih besar dari nilai Sig. (2-tailed) yakni 0,000 maka Ho ditolak dan Ha diterima. Berdasarkan hasil penelitian yang diperoleh maka dapat disimpulkan bahwa pembelajaran E- learning berbasis Moodle pada pembelajaran tematik dapat meningkatkan hasil belajar siswa kelas IV di MI Mangunsari Kota Salatiga.